NON-BIODEGRADATION OF POLYMERIZED POLYETHYLENE RADICALS AT SELECTED DUMPSITES IN KEFFI, NASARAWA STATE NIGERIA - Sufiyan I.; Salamatu A. E.; Alkali M (Journal CleanWAS)
Polythene and plastic bags pollutes the soil because these are non-biodegradable, and so, they cannot be degraded by the action of the microbes. Therefore, they remain in the soil and will pollute the soil. Polyethylene Terephthalate (PET) is therefore belongs to the class of polymers known as polyesters. In the natural environment, PET can be degraded by thermal oxidation, but hydrolytic cleavage and photo-oxidation initiated by UV light are more common under ambient conditions. In general, polyethylene offers excellent chemical and impact resistance, electrical properties and low coefficient of friction. It is considered a dielectric material. In addition, polyethylene are lightweight, easily processed and offer near-zero moisture absorption. In this study, selected dumps were covered in Keffi. The laboratory analysis was conducted. It was found out that there are two categories of Polyethylene with different properties, characteristics and functions. These are the High Density Polyethylene (HDPE) and Low Density Polyethylene (LDPE). The analysis revealed that T4 and T5 Isolate after drying contained more density of 8-9% degradation of high density polyethylene. While in the second tests of Low Density Polyethylene the T2, T7 and T8 have the highest coefficient of degradation. The residual plot of the dry weight polyethylene T9 has the highest weight in the model.